PrEP Chicago: A randomized controlled peer change agent intervention to promote the adoption of pre-exposure prophylaxis for HIV prevention among young Black men who have sex with men - Young, Lindsay E; Schumm, Phil; Alon, Leigh; Bouris, Alida; Ferreira, Matthew; Hill, Brandon; Khanna, Aditya S; Valente, Thomas W; Schneider, John A (Clinical trials (London, England), 2018)
Advances in biomedical prevention strategies such as pre-exposure prophylaxis (PrEP) represent a new opportunity for reducing HIV incidence among young Black men who have sex with men, for whom the number of new HIV infections continues to rise. However, studies have documented low rates of PrEP uptake in this community. Research suggests that the peer networks of young Black men who have sex with men play important roles in their sexual health decisions. PrEP Chicago is a randomized controlled trial network intervention designed to increase PrEP uptake among young Black men who have sex with men living in Chicago. The aims of this study are twofold. Aim 1 is to estimate the effectiveness of a peer change agent intervention for (1) increasing the number of referrals made to a PrEP information line, (2) increasing the rate of PrEP adoption among non-participant peers, and (3) increasing PrEP knowledge, attitudes, and intentions among participants. Aim 2 is to determine the individual and network variables that explain peer change agent effectiveness. PrEP Chicago is a social network intervention that utilizes the influence of peer change agents to link young Black men who have sex with men in Chicago to PrEP. Young Black men who have sex with men were recruited using respondent-driven sampling. Once screened for eligibility, participants were randomly assigned to either one of two treatment sequences: (1) intervention treatment in Year 1 followed by a minimal contact attention control in Year 2 or (2) the minimal contact attention control in Year 1 followed by treatment in Year 2. The treatment consists of a PrEP/peer change agent training workshop followed by booster calls for 12 months. The attention control consists of a sex diary activity designed to help participants assess sexual risk. Psychosocial, sexual health, and network data are collected from all participants at baseline and at 12- and 24-month follow-ups. In total, 423 participants aged 18-35 have been enrolled (more than 100% target enrollment) and have completed baseline data collection. A majority of participants in both intervention and control groups reported having heard of PrEP before enrolling in the study, yet also reported having had no current or prior experience taking PrEP. Statistical analyses await completion of Year 1 of the trial in March 2018. PrEP Chicago addresses a gap in HIV prevention research and intervention design by utilizing the existing social networks among young Black men who have sex with men as mechanisms for information diffusion, behavioral influence, social support, and empowerment. Therefore, interventions that leverage peer influence processes to facilitate PrEP uptake are promising strategies to improve sexual health engagement and overcome disparities in outcomes among this at-risk population.